2022
DOI: 10.1186/s12935-022-02621-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of icaritin derivative IC2 as an SCD-1 inhibitor with anti-breast cancer properties through induction of cell apoptosis

Abstract: Background Breast cancer is the most common malignancy affecting women, yet effective targets and related candidate compounds for breast cancer treatment are still lacking. The lipogenic enzyme, stearoyl-CoA desaturase-1 (SCD1), has been considered a potential target for breast cancer treatment. Icaritin (ICT), a prenylflavonoid derivative from the Traditional Chinese Medicine Epimedii Herba, has been reported to exert anticancer effects in various types of cancer. The purpose of the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…The ICT derivative IC2 ( Figure 1 ) inhibited SCD1 activity in a dose-dependent manner and induced apoptosis by the mitochondrial pathway in MCF-7 cells, which has been demonstrated in previous studies [ 10 ]. To understand whether autophagy played an important role in IC2-induced cell death, we examined the related indicators of autophagy.…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…The ICT derivative IC2 ( Figure 1 ) inhibited SCD1 activity in a dose-dependent manner and induced apoptosis by the mitochondrial pathway in MCF-7 cells, which has been demonstrated in previous studies [ 10 ]. To understand whether autophagy played an important role in IC2-induced cell death, we examined the related indicators of autophagy.…”
Section: Resultssupporting
confidence: 79%
“…Compared to ICT and other ICT derivates, IC2 showed the highest binding free energies (−114.9 kcal/mol) with SCD1, and the most significant inhibition of breast cancer cell proliferation. The subsequent experiments also confirmed that IC2 truly inhibited SCD1 activity in a dose-dependent manner and induced apoptosis in breast cancer cells [ 10 ]. Therefore, in this study, we further explored the mechanism of IC2-induced anti-breast cancer effect in vitro and in vivo, and we demonstrated that IC2 mediated cytoprotective autophagy in breast cancer cells through SCD1 inhibition, which provided a promising strategy for clinicians to explore the treatment of breast cancer.…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations